Dynamic behavior of single Fe atoms embedded in graphene - Markevich, A; Baldoni, M; Warner, J; Kirkland, A; Besley, E (American Chemical Society, 2016)
The effect of electron irradiation on the dynamic behavior of Fe atoms, embedded into monoS vacancy (Fe@MV) and diSvacancy (Fe@DV) defects in graphene, has been investigated using ab initio molecular dynamics. This study reveals the detailed mechanisms of transformation and migration of the Fe@MV and Fe@DV defects in graphene recently observed in aberration-corrected highSresolution transmission electron microscopy (ACSHRTEM) experiments [Nano Lett. 2013, 13, 1468]. An important atomicSscale insight into the dynamics of atomic Fe on graphene, unavailable to ACSHRTEM observations, has been provided. It was found that structural changes of the studied defects are induced by electron impacts on carbon atoms bonded to Fe. The threshold energies for ejection of these carbon atoms are significantly lower compared to that in pristine graphene. For electron impacts with the subSthreshold transferred energies, migration of the defects and flipping of Fe atoms between different sides of the graphene plane can occur. The stability of the Fe@MV defect under electron irradiation strongly depends on the substrate side position of Fe atom with respect to the direction of the electron beam. The Fe@DV → Fe@MV transformations take place spontaneously in the presence of carbon adSatoms, which are available in abundance on graphene in ACSHRTEM. The present study facilitates a greater general understanding of the dynamic behavior of substitutional metal atoms in graphene.